3266 Understanding epicardial adipose biology by imaging, transcriptomic, and lipidomic profiling. (27th March 2019) - Stojanovska, Jadranka; Tsodikov, Alex; Lumeng, Carey; Burant, Charles; Chenevert, Thomas
Abstract : OBJECTIVES/SPECIFIC AIMS: The study aims to understand if pro inflammatory epicardial white adipose phenotype is positively associated with coronary atherosclerosis, while the brown adipose phenotype is negatively associated. Primary outcome is association between epicardial fat fraction and coronary atherosclerosis and cardiac function. Secondary outcome is transcriptomic and lipidomic profiling between epicardial, extra pericardial, and subcutaneous depots and how these profiles correlate with fat fraction. METHODS/STUDY POPULATION: Recruited patients undergoing open-heart surgery provided informed consent at their second visit and underwent laboratory testing and imaging (cardiac magnetic resonance including water-fat imaging and coronary calcium computed tomography) prior to their surgery. Cardiac function such as cardiac chamber volume, mass, function, and strain, and depo-specific fat fraction were calculated from cardiac MR and Agatston calcium score and epicardial adipose volume from CT images. At the time of surgery, a tissue specimens from the epicardial, extrapericardial, and subcutaneous depots were obtained for transcriptomic and lipidomic analysis. Linear and logistic regression analyses adjusted for other variables were performed to evaluate significance level between variables. RESULTS/ANTICIPATED RESULTS: 37 subjects were enrolled in the study, 13 (35%) of which were women. Cardiac function and fat fraction was quantified in all patients, whereas tissue analyses were performed in 22 patients. Epicardial and extrapericardial fat fraction were independently associated with coronary atherosclerosis (p-value 0.01 and 0.04 respectively) Only epicardial fat fraction was negatively associated with global circumferential shortening of the left ventricle (0.03), while neither the extrapericardial fat fraction nor epicardial adipose volume were not (p =0.33 and 0.97 respectively) All three adipose depots have unique gene signatures with differentially expressed genes and pathways. RNA sequencing of epicardial, extrapericardial, and subcutaneous depots demonstrated tight clustering of epicardial and subcutaneous signatures based on PCA analysis (Figure 2). 19 lipid classes and 59 lipids showed differential expression between at least 2 of the fat depots (Figure 3). Hierarchal clustering of the lipids showed that epicardial and extrapericardial depots were more closely related than subcutaneous adipose. Plasmenyl-phosphatidylcholines, with an ether-linked fatty acid at the sn-1 position of the lipid, were higher in subcutaneous fat while most other lipids were higher in epicardial fat per tissue weight, such as ceramides (p=0.002). DISCUSSION/SIGNIFICANCE OF IMPACT: Epicardial, extrapericardial, and subcutaneous adipose depots express different lipidome and transcriptome signatures and different pathways. GSEA analysis demonstrated enrichment of genes related to antigen presentation and B cell immunity in epicardial compared to subcutaneous adipose tissue. Epicardial fat fraction is associated with coronary atherosclerosis and decreased left ventricular global circumferential shortening as an early predictor of decreased left ventricular stroke volume. Epicardial fat fraction is also associated with cermides which may play role in the development of coronary atherosclerosis and decreased cardiac function.